Presence of Pathogenic Leptospira spp. in an Urban Slum of the Colombian Caribbean: A One Health Approach - Mendoza SÃ¡nchez, Xilene; MartÃnez De La Rosa, Walter Angel; Parra Corzo, Deisy Liliana; RodrÃguez Sanjuan, Alexander; Varela Prieto, Lourdes Luz; Lagares GuzmÃ¡n, Alfredo (Revista Cubana de Medicina Tropical, 2020)
Objective: This study aims to describe the presence of pathogenic Leptospira and potential risk factors for leptospirosis in a marginal sector of the Colombian Caribbean, with a One Health approach. Methods: an exploratory study was carried out in a marginal sector of Soledad, a municipality located in the north coast of Colombia. Blood samples were taken from 83 subjects, who were also questioned about sociodemographic, clinical and ecological variables related to leptospirosis. The presence of IgM Anti-Leptospira antibodies in human serum was performed by ELISA. A total 53 synanthropic rodents were also captured using Sherman traps. Renal tissue samples were taken from rodents to identify pathogen Leptospira spp. by conventional PCR using specific primers. Results: IgM-anti-Leptospira was present in 30.12% of study subjects and pathogenic Leptospira spp. was identified in 7.55% of captured rodents. In the selected sample we found an association of positive cases with being a merchant, housewife and being in contact with pigs. Suboptimal hygienic-sanitary conditions were also evident in the study area. Conclusions: Our results show the circulation of pathogenic Leptospira spp. and exposure to human and ecological risk factors in a marginal sector (slum) of the Colombian Caribbean. We suggest to direct interventions in the human-animal-environment interface according to the One Health paradigm, considering extreme poverty as a determining factor for Leptospirosis occurrence.